The Pedagogy of the Pentateuch: The Undergraduate Classroom at a Large State University - Levinson, Bernard M. (Teaching theology and religion, 2025)
In response to the three questions suggested for this symposium on the pedagogy of the Pentateuch, I focus here less on what we teach and instead emphasize the values within our discipline. Students need to learn how to read the Bible as part of the humanities: as the work of thinkers who were reflecting on their place in the world and considering a system of values that the texts reflect. The Bible both embeds and requires a theory of reading, in which the redactors preserve conflicting viewpoints without erasing any perspective. Further, by contextualizing the Pentateuch in the ancient Near East, I teach students that the Bible provides a foundational document that lays the groundwork for modern views of ethics and legal history. It anticipates the origin of the ideas of equality and of constitutional thought (including rule of law and separation of powers). A new course in preparation, Scripture and Genocide: Rethinking the Bible after the Holocaust, probes the misuse of the Bible in genocidal regimes and ideologies.